2018
DOI: 10.1016/j.neuro.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Ahr and Cyp1a2 genotypes both affect susceptibility to motor deficits following gestational and lactational exposure to polychlorinated biphenyls

Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants known to cause adverse health effects and linked to neurological deficits in both human and animal studies. Children born to exposed mothers are at highest risk of learning and memory and motor deficits. We developed a mouse model that mimics human variation in the aryl hydrocarbon receptor and cytochrome P450 1A2 (CYP1A2) to determine if genetic variation increases susceptibility to developmental PCB exposure. In our previous studies, we found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…We have now extended those studies to PCB-induced motor dysfunction and found a similar role for the AHR and CYP1A2 (Stegman et al 2014; Colter et al 2017 submitted). The studies reported here were designed to identify the specific brain regions affected and the critical pathways involved in motor dysfunction.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We have now extended those studies to PCB-induced motor dysfunction and found a similar role for the AHR and CYP1A2 (Stegman et al 2014; Colter et al 2017 submitted). The studies reported here were designed to identify the specific brain regions affected and the critical pathways involved in motor dysfunction.…”
Section: Discussionmentioning
confidence: 57%
“…These were coplanar PCBs 77, 126, and 169 and non-coplanar PCBs 105, 118, 138, 153, and 180 (ULTRA Scientific, North Kingstown RI) dissolved in corn oil (Kroger). The coplanar PCB concentration insured persistent AHR activation through weaning in the high-affinity Ahr b mice, but not in poor-affinity Ahr d mice (Colter et al 2017 submitted). We used a mixture to better model human exposures because single congeners do not produce the same effects seen in human cohorts (Ulbrich and Stahlmann 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome P450s (CYPs) plays a key role in detoxification or activation of numerous xenobiotics ( 55 ). DL-PCBs bind and activate the aryl hydrocarbon receptor (AhR) to regulate three members of the CYP family: CYP1A1, CYP1A2 and CYP1B1 ( 58 ), which play an important role in the detoxification of PCB ( 59 ).…”
Section: Analysis Of Epidemiological Differencesmentioning
confidence: 99%
“…Some of the effects of EDCs already have well-characterized gene-environment interactions that modulate an organism’s susceptibility [ 16 , 17 , 18 , 19 ]. This is only a drop in the bucket of the many endocrine-disrupting chemicals that may participate in GxE.…”
Section: Introductionmentioning
confidence: 99%